Optimization of training load among weightlifters during pre-basic training - Orlov, A. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: develop and experimentally based methods of individualization of the training process weightlifters during pre-basic training for groups of first year students.